Board Of Directors Gender Diversity And Real Earnings Management: Does Female Board Of Director Matter? - Greska Redielano Ramadan (Universitas Muhammadiyah Malang, 2021)
The Board of directors' characteristic plays an important role as a monitoring mechanism in corporate governance. Previous research shows that gender could determine the existence of manager opportunistic behavior. The existence of females on the board of directors could reduce agency conflict such as earnings management. This research aimed examine gender diversity in explaining earnings management. The sample of this research is the non-financial company listed in Indonesia Stock Exchange (Idx) during 2014-2018. The research method conduct quantitative approach. We used multiple regression analysis to examine the association between board of director gender diversity on real earnings management. The result shows that gender diversity is negatively associated with earnings management. Gender diversity indicates that the number and percentage of female directors could reduce the level of real earnings management, especially through abnormal discretionary expenses. Secondly, there is no different level of real earnings management between firms with and without gender diversity in their board structures.